Analysis of Suitable Security Protocols for Apply a Model of Identity in the Civil Registry of Ecuador - Toapanta, Moisés; Mafla, Enrique; Orizaga, José (Review of Computer Engineering Research, 2016)
Different security protocols were analyzed are used for a centralized database with distributed architecture. The goal is identify adequate security protocols to mitigate the security of information through identity of a model without relying on technological infrastructures. In this phase the suitable security protocols for a model of identity authentication, authorization and auditing (AAA) was analyzed. Deductive method is used in exploratory research to analyze security protocols more used among the main mentioned: Feret, Kerberos, Radius, Dnssec, Ipsec, Pgp, Secure Rpc, Set, Ssl, Tls, Maille, Eap, Pap, Map, Diameter, Peap, among others. It turned out that security protocols should be adopted on a model of identity for a centralized data base. It was concluded that protocols and security algorithms must have a direct relation to the identity model; allowing mitigate the vulnerabilities and risks considering To mitigate the threats and risks of information with confidentiality, integrity and availability. The technological infrastructure should not influence the implementation of different security protocols.